The Fluorescent D-Amino Acid NADA as a Tool to Study the Conditional Activity of Transpeptidases in Escherichia coli - Montón Silva, Alejandro; Otten, Christian; Biboy, Jacob; Breukink, Eefjan; VanNieuwenhze, Michael; Vollmer, Waldemar; den Blaauwen, Tanneke (Frontiers in Microbiology, 2018)
The enzymes responsible for the synthesis of the peptidoglycan (PG) layer constitute a fundamental target for a large group of antibiotics. The family of lactam antibiotics inhibits the DD-transpeptidase (TPase) activity of the Penicillin Binding Proteins (PBPs), whereas its subgroup of carbapenems can also block the TPase activity of the LD-TPases. D-Ala fluorescent probes, such as NADA, are incorporated into the PG presumably by TPases in E. coli and can be used to study conditions that are required for their function. Of all LD-TPases of E. coli, only LdtD was able to incorporate NADA during exponential growth. Overproduction of LdtD caused NADA to be especially inserted at mid cell in the presence of LpoB-activated PBP1b and the class C PBP5. Using the NADA assay, we could confirm that LpoB activates PBP1b at mid cell and that CpoB regulates the activity of PBP1b in vivo. Overproduction of LdtD was able to partly compensate for the inhibition of the cell division specific class B PBP3 by aztreonam. We showed that class A PBP1c and the class C PBP6b cooperated with LdtD for NADA incorporation when PBP1b and PBP5 were absent, respectively. Besides, we proved that LdtD is active at pH 7.0 whereas LdtE and LdtF are more active in cells growing at pH 5.0 and they seem to cooperate synergistically. The NADA assay proved to be a useful tool for the analysis of the in vivo activities of the proteins involved in PG synthesis and our results provide additional evidence that the LD-TPases are involved in PG maintenance at different conditions.